(untitled) (Olhar de Professor, 2025)
This article intents to enhance the presence of the contemporary art in school as a promoter and a mobilizer thought, as an opening or a stance, more than an artistic act itself. The idea of “having the art within us” comes from the way a child expresses himself in front of plenty of supplies in an art room and the possibility of realizing the wish of “having ideas while thinking”. The aim is to build a conversation between this childish proposition and the production of contemporary visual artists such as: Carolina Caycedo, Gê Viana, Xadalu Tupã Jekupé. They invite to reflect about social and environmental issues in the present. Thinking about art is to experience new and other paths in school and in life, mobilizing senses and perceptions. As references for the design of this path thought, there is support on Luis Camnitzer (2018), Célia Xakriabá (2020), Ailton Krenak (2019; 2020) and the production of ArtVersa (FACED/UFRGS) group.